2005
DOI: 10.1007/s10490-005-1254-0
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Relationships for Customer Satisfaction in China: Interdependence and Cooperative Goals

Abstract: This study develops a model based on Deutsch’s theory of cooperation and competition to clarify the supply chain relationships and interactions that contribute to customer satisfaction. Results of structural equation analyses suggest that organizations and suppliers and organizations and distributors who recognize each other’s importance develop cooperative rather than competitive and independent goals. With cooperative goals, they come to trust each other and work for continuous improvement; these relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 76 publications
5
31
0
Order By: Relevance
“…Ramaseshan et al (2006) found that both coercive power and reward power had a positive effect on commitment, and Maloni and Benton likewise found a positive relationship between reward power and normative relationship commitment. Wong et al (2005), however, found that Chinese managers avoided opportunistic behavior because of the value placed on interpersonal relationships. Thus, there is a need for further testing of this relationship.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Ramaseshan et al (2006) found that both coercive power and reward power had a positive effect on commitment, and Maloni and Benton likewise found a positive relationship between reward power and normative relationship commitment. Wong et al (2005), however, found that Chinese managers avoided opportunistic behavior because of the value placed on interpersonal relationships. Thus, there is a need for further testing of this relationship.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Third, the Chinese business environment is under the heavy influence of Confucianism, which has endured as the basic social and political value system for over 2,000 years (Hwang, 1987). Therefore, guanxi, favor, and reciprocity are the common features embodied in the relationship between firms and their stakeholders such as governments in China (Tsang, 1998;Wong, Tjosvold, & Zhang, 2005).…”
Section: Buffering Bridgingmentioning
confidence: 99%
“…On the one hand, understanding face-giving and face-saving mechanisms are crucial in order to build trust in this low-trust culture, break the face barrier, and in addition to motivate local knowledge holders' involvement in knowledge sharing and integration (Hung, 2004). On the other hand, an embedded learning culture with strong emphasis on accountability, valuing local knowledge and trust (Chen and Chen, 2004;Dodgson, 1993;Fryxell, Dooley andLi, 2004, Porras, Clegg andCrawford, 2004;Wong, Tjosvold and Zhang, 2005;Zarraga and Bonache, 2003) will motivate articulation of tacit knowledge. In addition, rules, directions, tough task assignment and empowerment will all exert pressure for knowledge holders to share and utilise their ideas (Grant, 1997).…”
Section: A 'Pull and Push' Systemmentioning
confidence: 99%